Ethnopharmacological Approaches to Wound Repair - Akkol, Esra Küpeli; Afifi, Fatma U.; Hj. Baie, Saringat; Taranalli, Ashok D.; Anant, Shrikant (Hindawi Publishing Corporation, 2013)
Wound is breaking of the skin by a physical injury. Wound healing is a connective tissue response along with the repair process which immediately comes after the injury. It occurs as a sequence of phases such as haemostasis, inflammation, proliferation, and remodelling and causes series of interactions between the extracellular matrix, cytokine mediators, and different cell types. For rapid healing several medicinal plants were reported in ethnobotanical studies. Traditional remedies which claimed to have wound healing potential are widely used in developing countries due to their accessibility and low cost. However, these remedies should be evaluated for their efficacy and safety before their utilization. In this context, the papers selected for this special issue include scientifically evaluated information and lead to development of novel drugs for rapid healing of wounds.We would like to thank the authors for their contributions for this special issue. This special issue contains twelve papers. T. Lin et al. investigated the wound healing effect of tocopherol in diabetic rats.This study has proven thewound healing potential of tocopherol cream by increasing the rate of wound closure and total protein content significantly in diabetic condition.